2017
DOI: 10.1111/iej.12844
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analysis of 1‐year recall data from three root canal treatment outcome studies undertaken using cone beam computed tomography

Abstract: The proportions of favourable outcomes of primary root canal treatments and retreatments assessed with CBCT were lower when compared to periapical radiographs, and also lower than those historically reported by periapical radiograph-based outcome studies. Considering the very high favourable outcome of anterior teeth and premolars compared to molar teeth, future studies assessing the effect of new materials and techniques on the outcome of root canal treatments should be based on preoperative and postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 45 publications
1
31
0
2
Order By: Relevance
“…, Al‐Nuaimi et al . ). Detection of untreated canals has the potential to positively influence the outcome of retreatment or periradicular surgery of these teeth (Patel et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Al‐Nuaimi et al . ). Detection of untreated canals has the potential to positively influence the outcome of retreatment or periradicular surgery of these teeth (Patel et al .…”
Section: Discussionmentioning
confidence: 97%
“…This exam is especially useful for teeth with complex anatomy, such as molars, in which CBCT revealed the greater percentage of untreated canals in the present study (57% in maxillary and 26% in mandibular molars). Other studies have reported the superiority of CBCT over conventional periapical radiographs in revealing a greater failure rate in molar teeth (Patel et al 2012a, Al-Nuaimi et al 2018. Detection of untreated canals has the potential to positively influence the outcome of retreatment or periradicular surgery of these teeth (Patel et al 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, molar teeth had a significantly poorer success rate than premolar and anterior teeth (Al‐Nuaimi et al . ).…”
Section: Assessment Of Periapical Periodontitismentioning
confidence: 97%
“…Clinical studies comparing the detection of periapical lesions between CBCT and periapical radiographs (PR) in untreated and endodontically treated teethPatel et al CBCT in Endodonticsa review International Endodontic Journal, 52, 1138-1152 analysis of 354 root filled teeth (123 primary treatments and 231 retreatments), the success rate for root canal treatment was lower when assessed using CBCT compared to PR. Furthermore, molar teeth had a significantly poorer success rate than premolar and anterior teeth(Al-Nuaimi et al 2018). Fern andez et al…”
mentioning
confidence: 99%
“…The outcome of root canal treatment is assessed using clinical signs and symptoms, radiographic/CBCT imaging and histopathological evaluation (Lazarski et al , Ng et al , Al‐Nuaimi et al ). Many preoperative, intra‐operative and postoperative factors impact on the outcome of root canal treatment (Cabanillas‐Balsera et al ) with diabetes mellitus being a systemic condition that has been implicated in a greater incidence of post‐treatment endodontic disease, delayed healing and an increased prevalence of tooth extractions (Segura‐Egea et al ).…”
Section: Introductionmentioning
confidence: 99%